Regulatory proceedings of church property in court decisions - Pietrzak, Helena (Prawo Kanoniczne, 2024)
The regulation of property matters of the Roman Catholic Church after 1989 created the basis for recovery of goods that in earlier years (especially during the Polish People's Republic) the Church had lost to the state in an illegal or unjust manner. The most controversial issue was the out-of-court procedure of proceedings before the Property Commission, including the scope of real estate returns and the amount of compensation. The analysis of court decisions in the subject matter presents the contentious layer - the basis of claims, or the issue of ownership - legal titles based on civil and canon law in the past.